Toward Noninvasive Diagnosis of IgA Nephropathy: A Pilot Urinary Metabolomic and Proteomic Study - Neprasova, Michaela; Maixnerova, Dita; Novak, Jan; Reily, Colin; Julian, Bruce A; Boron, Jan; Novotny, Petr; Suchanek, Miloslav; Tesar, Vladimir; Kacer, Petr (Disease markers, 2016)
IgA nephropathy is diagnosed by renal biopsy, an invasive procedure with a risk of significant complications. Noninvasive approaches are needed for possible diagnostic purposes and especially for monitoring disease activity or responses to treatment. In this pilot project, we assessed the utility of urine samples as source of biomarkers of IgA nephropathy. We used spot urine specimens from 19 healthy controls, 11 patients with IgA nephropathy, and 8 renal-disease controls collected on day of renal biopsy. Urine samples were analyzed using untargeted metabolomic and targeted proteomic analyses by several experimental techniques: liquid chromatography coupled with mass spectrometry, immunomagnetic isolation of target proteins coupled with quantitation by mass spectrometry, and protein arrays. No single individual biomarker completely differentiated the three groups. Therefore, we tested the utility of several markers combined in a panel. Discriminant analysis revealed that combination of seven markers, three metabolites (dodecanal, 8-hydroxyguanosine, and leukotriene C4), three proteins (α1-antitrypsin, IgA-uromodulin complex, and galactose-deficient IgA1), and heparan sulfate, differentiated patients with IgA nephropathy from patients with other renal diseases and healthy controls. Future studies are needed to validate these preliminary findings and to determine the power of these urinary markers for assessment of responses to therapy.
Keywords: Male; biologické markery; Middle Aged; Biomarkers; uromodulin; proteom; Leukotriene C4; Uromodulin; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; alfa-1-antitrypsin; IgA nefropatie; Aldehydes; guanosin; aldehydy; Heparitin Sulfate; lidé; heparitinsulfát; ženské pohlaví; studie případů a kontrol; Humans; alpha 1-Antitrypsin; imunoglobulin A; Metabolome; metabolom; leukotrien C4; Female; Guanosine; Immunoglobulin A; Proteome; lidé středního věku; Glomerulonephritis, IGA